Analysis of Time Determinants Under The Conditions of Application of The Time Driven Activity Based Costing Method Aws - Alnujaimi Aws Saeed Mirdan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The studies of J. Lave and L. Silverman, which, with the help of the proximity technique,demonstrated that only through a closeness between time and space can relevant results be obtained toachieve a superior performance under the given conditions of the current health system, in our opinion,outlines the idea that the application of the Time-Driven Activity-Based Costing (TD-ABC) method is themost suitable solution. The complexity of TD-ABC operations is found in the time equations needed todetermine the resources consumed by each activity. Using these equations, it is easy to update the modelby adding an additional activity. This simplification would allow the multiplication of the activities to betreated without presenting difficulties in the distribution of resources. In fact, what we have here isclearly an "autonomous method of equivalence" that uses working time as a unit of equivalence. Themain objective of our concerns is to identify the determinants of the time required to start, perform andcomplete medical procedures in an ambulatory clinic organized in 15 medical offices. As a reaction to thecriticisms of some authors regarding the difficulty of measuring time for establishing the time drivers ofthe TD-ABC method, in the scientific approach carried out we tried to model the activity times with thehelp of the multiple regression model. We believe that the values ​​estimated and obtained with the help ofthe Automatic Linear Modeling factor analysis model eliminate the imperfection of the TD-ABC methodhighlighted by the authors S. Hoozée et al (2009) regarding subjectivity and instability in themeasurement of activity times.